Spatial temporal measures: a new parameter for planning - Hosny, Abdel Hady (AUC Knowledge Fountain, 2014)
With the increase complexity and competition in the construction market, contractors are forced to deliver larger scale projects in shorter durations. In order to do so, more concurrent activities are scheduled durations are crashed. Having a large number of concurrent activities with various crews increases the risk of workspace conflicts on sites, eventually affecting the productivity, time, cost and quality. Thus, there is an increasing attention to identify measures that are able to detect and analyze the possible workspace conflicts that would occur in a project in the planning stage before execution. Currently, practioners perform workspace analysis via expert judgment manually, which usually fails when the number of objects increases in a project. There have been previous attempts to creating frameworks to generate the workspaces and estimate the clashes. However, most studies did not provide a complete solution covering the whole process from the automated generation of the workspaces till the evaluation of the clashes. Also, the previous attempts clearly underestimated the value of the clashes giving a false indication of the true problem. Accordingly, this research proposes a new complete framework to detect, analyze and evaluate spatial temporal interferences in a project. The developed framework consists of 4 main modules: 4D Model Generator, Workspace Generator, Clash Detector and Clash Evaluator. These modules present methods for automating the generation of workspaces, clash detection mechanism and present a two level check clash magnitude estimator. The first check is performed on the days to identify the critical one that exceed the allowable tolerance levels, and the second check is performed on the activities to provide the user with a decision support system to optimize the clashes in a project. This study has been verified and validated. The first was by creating a test model, where the calculations were demonstrated and have led to the desired optimum solution. The latter attempt was by applying the framework via a developed software tool to a residential building as case study. The results showed improvement of an average of 20% in the first level check results. The results were presented to experts in the construction field whom have praised the work and acknowledged its usefulness.